(untitled) (Análisis Económico, 2018)
La preocupación de los economistas por la prosperidad de las naciones ha llevado al desarrollo de diversas teorías que tratan de explicar por qué algunos países son más competitivos que otros. Este trabajo pretende hacer una breve revisión de las diferentes teorías que han estudiado las fuentes de la ventaja competitiva de las naciones, así como, examinar la importancia de ésta para el logro de la prosperidad de las mismas y el papel que juega el Estado en el desarrollo de dicha ventaja. Clasificación JEL: F11, F20, F23, F31, F49. Abstract The concern of economists by the prosperity of nations has led to the development of different theories that attempt to explain the reasons for some countries being more competitive than others. The aim of this paper is to attempt an examination of the different theories that have studied the sources of national competitive advantages as also the importance that this had in their becoming prosperous; as well the role played by the state in said advantage.